Cu-TCPP modified carbon cloth reinforced resin-based friction material as well as preparation method and application thereof

By growing Cu-TCPP nanosheets on the surface of the carbon fiber cloth, combined with the synergistic effect of mechanical meshing and chemical bonding, the problem of insufficient interface bonding between carbon fiber and resin matrix is ​​solved, and the friction and wear performance and long-term stability of the friction material are significantly improved.

CN119912787APending Publication Date: 2025-05-02NORTHWESTERN POLYTECHNICAL UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510077362.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-17
Publication Date
2025-05-02

AI Technical Summary

Technical Problem

The interface bond between carbon fiber and resin matrix is ​​weak, resulting in insufficient friction and wear performance and long-term stability of carbon fiber-reinforced resin-based friction materials.

Method used

The interface bond between carbon fiber and resin is improved by growing layered Cu-TCPP nanosheets in situ on the surface of the carbon fiber cloth, and combining the synergistic effect of mechanical engagement and chemical bonding.

Benefits of technology

The friction and wear performance of friction materials is significantly improved, the friction coefficient is improved by 14.3%, the wear rate is reduced by 36.5%, and the long-term stability of the material is enhanced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119912787A_ABST
    Figure CN119912787A_ABST
Patent Text Reader

Abstract

The invention discloses a Cu-TCPP modified carbon cloth reinforced resin-based friction material and a preparation method and application, and belongs to the technical field of friction materials.The method comprises the steps that cupric nitrate trihydrate and polyvinylpyrrolidone are dissolved in N, N-dimethylformamide, meso-tetra (4-carboxyphenyl) porphin is dissolved in absolute ethyl alcohol, after mixing is conducted, a mixture is obtained, and the Cu-TCPP modified carbon cloth reinforced resin-based friction material is obtained; the Cu-TCPP modified carbon cloth reinforced resin-based friction material is prepared by the following steps: taking Cu-TCPP as a raw material, putting the Cu-TCPP modified carbon cloth reinforced resin-based friction material into carbon fiber cloth which is pre-treated and sewed into a column shape, carrying out solvothermal reaction, cleaning, freeze-drying, carrying out dipping treatment in a phenolic resin ethanol solution, drying, and carrying out hot-pressing curing. Lamellar Cu-TCPP is grafted on the surface of the carbon fiber, so that the roughness of the surface of the fiber can be increased by layered stacked nanosheets, and better mechanical engagement is formed between the carbon fiber and a resin matrix; active functional groups such as hydroxyl are introduced, carbon fibers and resin form chemical bonding in the hot pressing process, the interface performance is improved, the friction and wear performance of the friction material is improved, the dynamic friction factor is increased by 14.3%, and the wear rate is decreased by 36.5%.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of friction materials, and in particular relates to a Cu-TCPP modified carbon cloth reinforced resin-based friction material and a preparation method and application thereof. Background Art

[0002] Carbon fiber reinforced resin-based friction materials have emerged with the development of modern industry, especially the growing demand for high-performance friction materials in the fields of transportation and mechanical engineering. In the field of transportation, traditional friction materials are difficult to meet the requirements of high-performance vehicle braking systems; in mechanical engineering, various types of high-precision machinery require stable friction components for precise control of the mechanical system during operation. Therefore, it is particularly important to improve the friction performance of fiber-reinforced resin-based friction materials. Appropriate modification of the carbon fiber surface can effectively enhance the interfacial adhesion between the carbon fiber and the resin matrix, thereby significantly improving the friction and wear performance of the composite material. However, due to its hydrophobic and smooth surface characteristics, carbon fiber has a significant modulus difference with the resin matrix, which often leads to insufficient bonding between the two.

[0003] The Chinese patent "A sizing agent for carbon fiber modification, its preparation method and its use method" with publication number CN118186781A modifies carbon fiber with a sizing agent to improve its mechanical properties such as toughness and tensile strength. It can also act as a lubricant to reduce friction between fibers and reduce the phenomenon of breakage due to friction, bending and other reasons during processing; at the same time, the sizing agent also makes the carbon fiber easier to impregnate with resin and improve its interlaminar shear strength. However, the firmness of the sizing agent and carbon fiber is challenged. During long-term use, especially when facing complex environmental conditions (such as continuous external force, temperature changes, etc.), the sizing agent may gradually separate from the surface of the carbon fiber, resulting in the durability of the modification effect being impaired, thereby affecting the stability of the overall performance of the carbon fiber reinforced composite material. The Chinese patent "A method for grafting hyperbranched polymers on the surface of carbon fiber" with publication number CN107266712A discloses a grafting method on the surface of carbon fiber. The chemical grafting method is used to first graft silane coupling agent on the surface of carbon fiber, introduce amine group as nucleating agent, and then graft succinic anhydride and diethanolamine to generate carbon fiber surface grafted hyperbranched polymer with hydroxyl group at the end, which can eventually increase the polar groups on the surface of carbon fiber, increase its surface energy, improve the wettability between the surface of carbon fiber and matrix, and thus improve the overall performance of composite materials. However, the carbon fiber grafted hyperbranched polymer has poor dispersibility and is prone to agglomeration; if the grafting process is not properly controlled, it may have an adverse effect on the intrinsic structure of carbon fiber; the reaction is complex, and the grafting reaction requires precise control of conditions; the synthesis cost is high, which is not conducive to large-scale application.

[0004] In view of the problem of weak interface bonding between carbon fiber and resin matrix, it is urgent to find a new modification method to strengthen the interface bonding between carbon fiber and resin matrix, so as to effectively improve the friction and wear performance and long-term stability of carbon fiber reinforced resin-based friction materials. Summary of the invention

[0005] In order to overcome the shortcomings of the above-mentioned prior art, the purpose of the present invention is to provide a Cu-TCPP modified carbon cloth reinforced resin-based friction material and a preparation method and application, so as to solve the technical problem of how to enhance the interface bonding between carbon fiber and resin matrix, thereby effectively improving the friction and wear performance and long-term stability of carbon fiber reinforced resin-based friction material.

[0006] In order to achieve the above object, the present invention adopts the following technical solutions: The invention discloses a method for preparing a Cu-TCPP modified carbon cloth reinforced resin-based friction material, comprising the following steps: 1) Dissolve copper nitrate trihydrate and polyvinyl pyrrolidone in N,N-dimethylformamide to obtain a mixed solution A; dissolve meso-tetrakis(4-carboxyphenyl)porphine in anhydrous ethanol to obtain a mixed solution B; mix the mixed solution A and the mixed solution B, stir and react, and obtain a mixed solution C; 2) The pretreated carbon fiber cloth is sewn into a column and placed in the mixed solution C for solvothermal reaction. After the reaction is completed, it is washed alternately with anhydrous ethanol and N, N-dimethylformamide, and freeze-dried to obtain Cu-TCPP modified carbon cloth; 3) The Cu-TCPP modified carbon cloth is impregnated in a phenolic resin ethanol solution, dried, and then hot-pressed to obtain a Cu-TCPP modified carbon cloth reinforced resin-based friction material.

[0007] Preferably, in step 1), the usage ratio of copper nitrate trihydrate, polyvinyl pyrrolidone, N,N-dimethylformamide, meso-tetrakis(4-carboxyphenyl)porphine and anhydrous ethanol is (0.072-0.1152) g: (0.2-0.32) g: 45 ml: (0.08-0.128) g: 15 ml.

[0008] Preferably, in step 1), the speed of the stirring reaction is 800-1000 r / min.

[0009] Preferably, in step 2), the pretreatment of the carbon fiber cloth comprises: firstly soaking the carbon fiber cloth in acetone, washing it once with deionized water, drying it once, then oxidizing it in a nitric acid solution, washing it twice with deionized water, and drying it twice.

[0010] Further preferably, in step 2), the soaking time is 48-76 hours; the mass fraction of the nitric acid solution is 68%; the temperature of the oxidation treatment is 75-95° C.; and the time is 3-5 hours.

[0011] Preferably, in step 2), the temperature of the solvent thermal reaction is 70-90° C. and the time is 12-24 h.

[0012] Preferably, in step 3), the immersion pressure is 0.08-0.1 MPa, and the immersion time is 10-24 h.

[0013] Preferably, in step 3), the temperature of hot pressing curing is 170-190° C., the pressure is 4-6 MPa, and the curing time is 8-10 min.

[0014] The present invention also discloses a Cu-TCPP modified carbon cloth reinforced resin-based friction material, which is prepared by the above-mentioned preparation method of the Cu-TCPP modified carbon cloth reinforced resin-based friction material. In the Cu-TCPP modified carbon cloth reinforced resin-based friction material, the mass fraction of resin is 24%-26%.

[0015] The invention also discloses the application of the Cu-TCPP modified carbon cloth reinforced resin-based friction material prepared by the preparation method of the Cu-TCPP modified carbon cloth reinforced resin-based friction material in vehicle braking.

[0016] Compared with the prior art, the present invention has the following beneficial effects: The invention discloses a preparation method of a Cu-TCPP modified carbon cloth reinforced resin-based friction material, firstly, the carbon fiber cloth is surface pretreated, lamellar Cu-TCPP nanosheets are in-situ grown on the surface of the carbon fiber cloth by solvent thermal reaction, the carbon fiber cloth loaded with lamellar Cu-TCPP nanosheets is alternately cleaned with N, N-dimethylformamide and anhydrous ethanol, freeze-dried, impregnated, and hot-pressed to obtain the Cu-TCPP modified carbon cloth reinforced resin-based friction material. The invention grafts Cu-TCPP on the surface of the carbon fiber to improve the interface bonding between the carbon fiber and the resin, and improves the friction and wear performance of the friction material by means of the synergistic effect of mechanical meshing and chemical bonding. By regulating the concentration of reactants and the amount of polyvinyl pyrrolidone added, lamellar Cu-TCPP is in-situ grown on the carbon fiber cloth, which is conducive to increasing the roughness of the fiber surface, so that the carbon fiber and the resin matrix form better mechanical meshing; active functional groups such as hydroxyl and carboxyl are introduced on the carbon fiber, and the carbon fiber and the resin form chemical bonding during the hot pressing process, which improves the interface performance, thereby improving the friction and wear performance of the friction material. The Cu-TCPP modified carbon cloth reinforced resin-based friction material prepared by the present invention has the advantages of simple process, low cost and excellent performance. Compared with the unmodified sample, the modified composite material has excellent friction and wear performance, the friction coefficient is increased by 14.3%; and the wear rate is reduced by 36.5%.

[0017] Furthermore, the dosage ratio of copper nitrate trihydrate, polyvinyl pyrrolidone, N,N-dimethylformamide, meso-tetrakis (4-carboxyphenyl) porphine and anhydrous ethanol is (0.072-0.1152) g: (0.2-0.32) g: 45 ml: (0.08-0.128) g: 15 ml; the precise raw material ratio ensures that the reaction can be carried out efficiently and stably, avoiding the inadequate reaction caused by the waste or insufficient raw materials. By optimizing the ratio of each raw material, the growth rate, morphology and distribution of Cu-TCPP nanosheets can be regulated, thereby optimizing the performance of the final friction material.

[0018] Furthermore, the speed of the stirring reaction is 800-1000r / min, which is conducive to the uniform mixing of the raw materials and the full progress of the reaction. Too low a speed may lead to uneven distribution of the reactants and affect the growth of Cu-TCPP nanosheets; while too high a speed may bring unnecessary energy consumption and mechanical damage. The speed setting in this range not only ensures the reaction efficiency, but also avoids potential problems.

[0019] Furthermore, the pretreatment step effectively removed impurities and oil stains on the surface of the carbon fiber cloth, improving its surface cleanliness and activity. The nitric acid oxidation treatment further increased the roughness and oxygen-containing functional groups on the carbon fiber surface, which was beneficial to the subsequent growth of Cu-TCPP nanosheets and their combination with the resin.

[0020] Furthermore, the soaking time is 48-76 hours; the mass fraction of the nitric acid solution is 68%; the reasonable soaking time and nitric acid concentration can ensure that the carbon fiber is fully oxidized without excessively damaging its structure. This range setting not only ensures the oxidation effect, but also avoids the decline of carbon fiber performance.

[0021] Furthermore, the oxidation treatment temperature is 75-95°C and the time is 3-5h. Appropriate oxidation temperature and time can control the rate and degree of oxidation reaction and ensure that the carbon fiber surface is appropriately modified. Too high temperature or too long time may cause the destruction of the carbon fiber structure, while too low temperature may lead to insufficient oxidation.

[0022] Furthermore, the solvothermal reaction temperature is 70-90°C and the time is 12-24h. This range of solvothermal reaction conditions is conducive to the stable growth of Cu-TCPP nanosheets on the carbon fiber surface. Appropriate temperature and time can ensure that the reaction proceeds fully while avoiding unnecessary energy consumption and the generation of reaction by-products.

[0023] Furthermore, the impregnation pressure is 0.08-0.1MPa, and the impregnation time is 10-24 hours; appropriate impregnation pressure and time can ensure that the resin fully penetrates into the pores of the carbon fiber cloth to form a compact composite material structure. Too low pressure or too short time may lead to insufficient impregnation and affect the performance of the composite material; while too high pressure or too long time may bring unnecessary energy consumption and cost.

[0024] Furthermore, the temperature of hot pressing curing is 170-190°C, the pressure is 4-6MPa, and the curing time is 8-10min; this range of hot pressing curing conditions can ensure the full curing of the resin and form a stable composite material structure. Appropriate temperature and pressure can accelerate the curing process and improve production efficiency; at the same time, avoid excessive temperature and pressure to damage the carbon fiber and resin.

[0025] Furthermore, in the Cu-TCPP modified carbon cloth reinforced resin-based friction material, the mass fraction of resin is 24%-26%; by optimizing the resin content, it can be ensured that the composite material has the best mechanical properties, friction properties and heat resistance. Too low a resin content may lead to a loose structure of the composite material and reduced performance; while too high a resin content may increase costs and reduce the reinforcing effect of carbon fiber. This range of resin content setting not only ensures the performance of the composite material, but also controls the cost.

[0026] The present invention also discloses a Cu-TCPP modified carbon cloth reinforced resin-based friction material, which significantly improves the interface bonding between carbon fiber and resin by grafting Cu-TCPP onto the surface of carbon fiber. This improvement is achieved not only through mechanical engagement, but also by enhancing the interaction force between the two through chemical bonding. The synergistic effect enables the friction material to transfer stress more effectively during braking, thereby improving the friction coefficient and wear resistance. The increase in the friction coefficient enables the braking system to generate braking force more quickly and stably, shorten the braking distance, and improve the safety of the vehicle. The decrease in wear rate prolongs the service life of the friction material, reduces the frequency of maintenance and replacement, and reduces the operating cost of the vehicle.

[0027] The present invention also discloses the application of the Cu-TCPP modified carbon cloth reinforced resin-based friction material prepared by the preparation method of the above-mentioned Cu-TCPP modified carbon cloth reinforced resin-based friction material in vehicle braking. The modified friction material can generate braking force more stably during braking, reduce braking vibration and noise, and improve driving comfort and safety. The reduction in wear rate enables the friction material of the braking system to maintain its performance for a longer time, reduces the frequency of maintenance and replacement, and reduces the operating cost and maintenance cost of the vehicle. By optimizing the content of the resin and the overall performance of the composite material, the modified friction material can better adapt to different braking conditions (such as high temperature, high speed, wet and slippery, etc.), and improve the braking performance and safety of the vehicle. Due to the reduced frequency of maintenance and replacement and the improved utilization efficiency of raw materials, the modified friction material also has certain advantages in environmental protection and sustainability. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 The SEM photos of the Cu-TCPP modified carbon cloth prepared in Example 1 of the present invention, wherein (a) is the original carbon fiber cloth, and (b) is the Cu-TCPP modified carbon cloth prepared in Example 1.

[0029] Figure 2 This is the FTIR analysis chart of the Cu-TCPP modified carbon cloth prepared in Example 1 of the present invention, wherein CF is the original carbon fiber cloth; CF / Cu-TCPP is the Cu-TCPP modified carbon cloth prepared in Example 1.

[0030] Figure 3 It is a comparison chart of the continuous friction coefficient of the Cu-TCPP modified carbon cloth reinforced resin-based friction material prepared in Example 1 of the present invention and the unmodified carbon cloth reinforced resin-based friction material prepared in Comparative Example 1, wherein C1 is the unmodified carbon cloth reinforced resin-based friction material prepared in Comparative Example 1, and C2 is the Cu-TCPP modified carbon cloth reinforced resin-based friction material prepared in Example 1.

[0031] Figure 4It is a comparison chart of the wear rates of the Cu-TCPP modified carbon cloth reinforced resin-based friction material prepared in Example 1 of the present invention and the unmodified carbon cloth reinforced resin-based friction material prepared in Comparative Example 1, wherein C1 is the unmodified carbon cloth reinforced resin-based friction material prepared in Comparative Example 1, and C2 is the Cu-TCPP modified carbon cloth reinforced resin-based friction material prepared in Example 1. DETAILED DESCRIPTION

[0032] The technical solution of the present invention will be described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0033] In the present invention, unless otherwise specified, all the embodiments and preferred implementation methods mentioned herein can be combined with each other to form a new technical solution.

[0034] In the present invention, unless otherwise specified, all technical features and preferred features mentioned herein can be combined with each other to form a new technical solution.

[0035] In the present invention, unless otherwise specified, percentage (%) or part refers to the weight percentage or weight part relative to the composition.

[0036] In the present invention, unless otherwise specified, the components or preferred components involved can be combined with each other to form a new technical solution.

[0037] In the present invention, unless otherwise specified, the numerical range "a~b" represents an abbreviation of any real number combination between a and b, where a and b are real numbers. For example, the numerical range "6~22" means that all real numbers between "6~22" have been listed in this document, and "6~22" is just an abbreviation of these numerical combinations.

[0038] The “range” disclosed in the present invention is in the form of a lower limit and an upper limit, which can be one or more lower limits, and one or more upper limits, respectively.

[0039] In the present invention, the term "and / or" used herein refers to any combination and all possible combinations of one or more of the associated listed items, and includes these combinations.

[0040] In the present invention, unless otherwise specified, each reaction or operation step can be carried out sequentially or in accordance with the sequence. Preferably, the reaction method herein is carried out sequentially.

[0041] Unless otherwise specified, the professional and scientific terms used herein have the same meanings as those familiar to those skilled in the art. In addition, any method or material similar or equivalent to the described content may also be applied to the present invention.

[0042] The present invention provides a Cu-TCPP modified carbon cloth reinforced resin-based friction material, comprising the following steps: Step 1: Soak the carbon fiber cloth in acetone for 48-76 hours to remove the sizing and impurities on the surface, wash it repeatedly with deionized water and dry it for later use; Step 2: The carbon fiber cloth obtained in step 1 is oxidized in a nitric acid solution with a mass fraction of 68% at 75-95° C. for 3-5 hours to enhance the active sites on the surface of the carbon fiber cloth, and then the carbon fiber cloth is repeatedly washed with deionized water and dried for later use; Step 3: Dissolve 0.072-0.1152g of copper nitrate trihydrate and 0.2-0.32g of polyvinyl pyrrolidone in 45ml of N, N-dimethylformamide to obtain a mixed solution A for ultrasonic treatment, dissolve 0.08-0.128g of medium-tetrakis (4-carboxyphenyl) porphine in 15ml of anhydrous ethanol to obtain a mixed solution B for ultrasonic treatment, and mix the mixed solution A and the mixed solution B by magnetic stirring, and control the speed to 800-1000r / min to obtain a mixed solution C. The 3-4g carbon fiber cloth obtained in step 2 is sewn into a column and placed in a polytetrafluoroethylene liner containing mixed solution C at 70-90°C for 12-24h to perform a solvent thermal reaction. After the reaction is completed, the carbon fiber cloth is repeatedly washed with anhydrous ethanol and N, N-dimethylformamide to remove unreacted monomers and Cu-TCPP not grafted on the surface of the carbon fiber cloth, and freeze-dried to obtain Cu-TCPP modified carbon fiber cloth; Step 4: The Cu-TCPP modified carbon fiber cloth obtained in step 3 is impregnated in a phenolic resin ethanol solution, the impregnation pressure is 0.08-0.1MPa, the impregnation time is 10-24 h; the mass fraction of the resin is controlled to be 24%-26%. After impregnation, the sample is dried and hot-pressed and cured in a vulcanizer to obtain a Cu-TCPP modified carbon cloth reinforced resin-based friction material. The process parameters of hot-press curing in a vulcanizer are: temperature 170-190℃, pressure 4-6MPa, and curing time 8-10min.

[0043] The present invention utilizes solvent thermal reaction to in-situ grow lamellar Cu-TCPP nanosheets on the surface of carbon fiber cloth, and combines subsequent steps such as cleaning, freeze drying, impregnation treatment and hot pressing curing to successfully prepare a Cu-TCPP modified carbon cloth reinforced resin-based friction material with significantly improved performance. Not only does it fundamentally improve the interface bonding state between the carbon fiber and the resin matrix, but also the lamellar Cu-TCPP is grafted on the surface of the carbon fiber. The layered nanosheets are conducive to increasing the roughness of the fiber surface, so that the carbon fiber and the resin matrix form better mechanical meshing; by introducing Cu-TCPP nanosheets and the active functional groups they carry, the dual enhancement of mechanical meshing and chemical bonding is achieved, thereby greatly improving the wear resistance, heat resistance, mechanical strength and stability of the friction material. By introducing active functional groups such as hydroxyl groups, the carbon fiber and the resin form chemical bonds during the hot pressing process, which improves the interface performance, thereby improving the friction and wear performance of the friction material, and the dynamic friction coefficient increases by 14.3% and the wear rate decreases by 36.5%. Moreover, the modification process is also highly flexible and controllable. By adjusting the reaction parameters and post-processing conditions, the growth morphology, distribution density and bonding mode of Cu-TCPP nanosheets with carbon fibers can be precisely controlled to meet the stringent requirements of different application scenarios for the performance of friction materials. In addition, the entire preparation process is green and environmentally friendly, and the solvents and raw materials used can be recycled, which is in line with the concept of sustainable development. Therefore, the present invention not only opens up a new path for the research and development of high-performance friction materials, but also makes important contributions to promoting scientific and technological progress and industrial upgrading in the friction material industry. By reinforcing the resin-based friction material with Cu-TCPP-modified carbon cloth, the interface bonding between carbon fiber and resin is significantly improved, and the friction coefficient and wear resistance of the friction material are improved, thereby achieving more stable and efficient braking performance in vehicle braking applications, while reducing operating costs and maintenance frequency, showing excellent comprehensive performance and environmental advantages.

[0044] In order to make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, rather than all of the embodiments. The components of the embodiments of the present invention described and shown in the drawings here can usually be arranged and designed in various different configurations. Therefore, the following detailed description of the embodiments of the present invention provided in the drawings is not intended to limit the scope of the claimed invention, but merely represents selected embodiments of the present invention. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0045] Example 1 A method for preparing a Cu-TCPP modified carbon cloth reinforced resin-based friction material comprises the following steps: Step 1: Soak 4g of carbon fiber cloth in acetone at room temperature for 48 hours to remove surface sizing and impurities, wash it repeatedly with deionized water three to four times, and then dry it for use; Step 2: The carbon fiber cloth obtained in step 1 is subjected to oxidation treatment in a nitric acid solution with a volume fraction of 68%, and the reaction conditions are 90° C. and 3 h to enhance the active sites on the surface of the carbon fiber cloth, and then the carbon fiber cloth is repeatedly washed with deionized water and dried for later use; Step 3: at room temperature, dissolve 0.072 g of copper nitrate trihydrate and 0.32 g of polyvinyl pyrrolidone in 45 ml of N,N-dimethylformamide to obtain a mixed solution A, and perform ultrasonic treatment on the mixed solution A to uniformly disperse the copper nitrate and polyvinyl pyrrolidone in the mixed solution A; Step 4: dissolving 0.08 g of meso-tetrakis(4-carboxyphenyl)porphine in 15 ml of anhydrous ethanol to obtain a mixed solution B, and subjecting the mixed solution B to ultrasonic treatment to uniformly disperse meso-tetrakis(4-carboxyphenyl)porphine ketone in the mixed solution B; Step 5: Mixing the mixed solution A and the mixed solution B by magnetic stirring to obtain a mixed solution C, the magnetic stirring speed being 900 r / min; Step 6: Inject the mixed solution C and the carbon fiber cloth into a 100 mL polytetrafluoroethylene liner, and then fix the liner in a matching stainless steel reactor; Step 7: Fix the stainless steel reactor containing the mixed solution C and the carbon fiber cloth in a homogeneous reactor and react for 24 hours at 80° C. and a rotation speed of 54 r / min to obtain a grafted Cu-TCPP carbon fiber cloth; The Cu-TCPP grafted carbon fiber cloth obtained in step 7 is washed three times with N,N-dimethylformamide and anhydrous ethanol to remove unreacted monomers and Cu-TCPP not grafted on the carbon fiber cloth, and then freeze-dried to obtain a Cu-TCPP modified carbon fiber cloth; The Cu-TCPP modified carbon fiber cloth was vacuum impregnated in a phenolic resin ethanol solution with a mass fraction of 24%. The impregnation conditions were: pressure of 0.09 MPa at room temperature and impregnation time of 12 h. The impregnated preform was placed in an oven and then dried, and then hot-pressed and cured in a vulcanizer to obtain a Cu-TCPP modified carbon cloth reinforced resin-based friction material. The hot-pressing curing conditions were: temperature 170°C, pressure 5MPa, and curing time 10min. The friction coefficient of the Cu-TCPP modified carbon cloth reinforced resin-based friction material was 0.104; the wear rate was 4.38×10 -12 m 3 / (N·m).

[0046] Example 2 A method for preparing a Cu-TCPP modified carbon cloth reinforced resin-based friction material comprises the following steps: Step 1: Soak 3g of carbon fiber cloth in acetone at room temperature for 52 hours to remove surface sizing and impurities, wash it repeatedly with deionized water three to four times, and then dry it for later use; Step 2: The carbon fiber cloth obtained in step 1 is subjected to oxidation treatment in a nitric acid solution with a volume fraction of 68%, and the reaction conditions are 75° C. and 3.5 h to enhance the active sites on the surface of the carbon fiber cloth, and then the carbon fiber cloth is repeatedly washed with deionized water and dried for later use; Step 3: at room temperature, dissolve 0.1152 g of copper nitrate trihydrate and 0.32 g of polyvinyl pyrrolidone in 45 ml of N,N-dimethylformamide to obtain a mixed solution A, and perform ultrasonic treatment on the mixed solution A to uniformly disperse the copper nitrate and polyvinyl pyrrolidone in the mixed solution A; Step 4: dissolving 0.128 g of meso-tetrakis(4-carboxyphenyl)porphine in 15 ml of anhydrous ethanol to obtain a mixed solution B, and subjecting the mixed solution to ultrasonic treatment to uniformly disperse meso-tetrakis(4-carboxyphenyl)porphine ketone in the mixed solution B; Step 5: Mixing the mixed solution A and the mixed solution B by magnetic stirring to obtain a mixed solution C, the magnetic stirring speed being 920 r / min; Step 6: Inject the mixed solution C and the carbon fiber cloth into a 100 mL polytetrafluoroethylene liner, and then fix the liner in a matching stainless steel reactor; Step 7: Fix the stainless steel reactor containing the mixed solution C and the carbon fiber cloth in a homogeneous reactor and react for 12 hours at 70° C. and a rotation speed of 50 r / min to obtain a grafted Cu-TCPP carbon fiber cloth; The Cu-TCPP grafted carbon fiber cloth obtained in step 7 is washed 4 times with N,N-dimethylformamide and anhydrous ethanol to remove unreacted monomers and Cu-TCPP not grafted on the carbon fiber cloth, and then freeze-dried to obtain a Cu-TCPP modified carbon fiber cloth; The Cu-TCPP modified carbon fiber cloth was vacuum impregnated in a phenolic resin ethanol solution with a mass fraction of 25%. The impregnation conditions were: pressure of 0.08 MPa at room temperature and impregnation time of 10 h. The impregnated preform was placed in an oven and then dried, and then hot-pressed and cured in a vulcanizer to obtain a Cu-TCPP modified carbon cloth reinforced resin-based friction material. The hot-pressing curing conditions were: temperature 190°C, pressure 4MPa, and curing time 8min. The friction coefficient of the Cu-TCPP modified carbon cloth reinforced resin-based friction material was 0.102; the wear rate was 4.46×10 -12 m 3 / (N·m).

[0047] Example 3 A method for preparing a Cu-TCPP modified carbon cloth reinforced resin-based friction material comprises the following steps: Step 1: Soak 3.5g of carbon fiber cloth in acetone at room temperature for 76 hours to remove surface sizing and impurities, wash it repeatedly with deionized water three to four times, and then dry it for use; Step 2: The carbon fiber cloth obtained in step 1 is subjected to oxidation treatment in a nitric acid solution with a volume fraction of 68%, and the reaction conditions are 95° C. and 5 h to enhance the active sites on the surface of the carbon fiber cloth, and then the carbon fiber cloth is repeatedly washed with deionized water and dried for later use; Step 3: at room temperature, dissolve 0.1052 g of copper nitrate trihydrate and 0.25 g of polyvinyl pyrrolidone in 45 ml of N,N-dimethylformamide to obtain a mixed solution A, and perform ultrasonic treatment on the mixed solution A to uniformly disperse the copper nitrate and polyvinyl pyrrolidone in the mixed solution A; Step 4: dissolving 0.126 g of meso-tetrakis(4-carboxyphenyl)porphine in 15 ml of anhydrous ethanol to obtain a mixed solution B, and subjecting the mixed solution B to ultrasonic treatment to uniformly disperse meso-tetrakis(4-carboxyphenyl)porphine ketone in the mixed solution B; Step 5: Mixing the mixed solution A and the mixed solution B by magnetic stirring to obtain a mixed solution C, the magnetic stirring speed being 800 r / min; Step 6: Inject the mixed solution C and the carbon fiber cloth into a 100 mL polytetrafluoroethylene liner, and then fix the liner in a matching stainless steel reactor; Step 7: Fix the stainless steel reactor containing the mixed solution C and the carbon fiber cloth in a homogeneous reactor and react for 23 hours at 90° C. and a rotation speed of 60 r / min to obtain a grafted Cu-TCPP carbon fiber cloth; The Cu-TCPP grafted carbon fiber cloth obtained in step 7 is washed three times with N,N-dimethylformamide and anhydrous ethanol to remove unreacted monomers and Cu-TCPP not grafted on the carbon fiber cloth, and then freeze-dried to obtain a Cu-TCPP modified carbon fiber cloth; The Cu-TCPP modified carbon fiber cloth was vacuum impregnated in a phenolic resin ethanol solution with a mass fraction of 26%. The impregnation conditions were: pressure of 0.1 MPa at room temperature and impregnation time of 15 h. The impregnated preform was placed in an oven and dried, and then hot-pressed and cured in a vulcanizer to obtain a Cu-TCPP modified carbon cloth reinforced resin-based friction material. The hot-pressing curing conditions were: temperature 175°C, pressure 5MPa, and curing time 9min. The friction coefficient of the Cu-TCPP modified carbon cloth reinforced resin-based friction material was 0.103; the wear rate was 4.79×10 -12 m 3 / (N·m).

[0048] Example 4 A method for preparing a Cu-TCPP modified carbon cloth reinforced resin-based friction material comprises the following steps: Step 1: Soak 3.5g of carbon fiber cloth in acetone at room temperature for 55 hours to remove surface sizing and impurities, wash it repeatedly with deionized water three to four times, and then dry it for use; Step 2: The carbon fiber cloth obtained in step 1 is subjected to oxidation treatment in a nitric acid solution with a volume fraction of 68%, and the reaction conditions are 75° C. and 3.5 h to enhance the active sites on the surface of the carbon fiber cloth, and then the carbon fiber cloth is repeatedly washed with deionized water and dried for later use; Step 3: at room temperature, dissolve 0.072 g of copper nitrate trihydrate and 0.2 g of polyvinyl pyrrolidone in 45 ml of N,N-dimethylformamide to obtain a mixed solution A, and perform ultrasonic treatment on the mixed solution A to uniformly disperse the copper nitrate and polyvinyl pyrrolidone in the mixed solution A; Step 4: dissolving 0.08 g of meso-tetrakis(4-carboxyphenyl)porphine in 15 ml of anhydrous ethanol to obtain a mixed solution B, and subjecting the mixed solution B to ultrasonic treatment to uniformly disperse meso-tetrakis(4-carboxyphenyl)porphine ketone in the mixed solution B; Step 5: Mixing the mixed solution A and the mixed solution B by magnetic stirring to obtain a mixed solution C, wherein the magnetic stirring speed is 1000 r / min; Step 6: Inject the mixed solution C and the carbon fiber cloth into a 100 mL polytetrafluoroethylene liner, and then fix the liner in a matching stainless steel reactor; Step 7: Fix the stainless steel reactor containing the mixed solution C and the carbon fiber cloth in a homogeneous reactor and react for 18 hours at 70° C. and a rotation speed of 55 r / min to obtain a grafted Cu-TCPP carbon fiber cloth; The Cu-TCPP grafted carbon fiber cloth obtained in step 7 is washed 4 times with N,N-dimethylformamide and anhydrous ethanol to remove unreacted monomers and Cu-TCPP not grafted on the carbon fiber cloth, and then freeze-dried to obtain a Cu-TCPP modified carbon fiber cloth; The Cu-TCPP modified carbon fiber cloth was vacuum impregnated in a phenolic resin ethanol solution with a mass fraction of 25%. The impregnation conditions were: pressure of 0.08 MPa at room temperature and impregnation time of 24 h. The impregnated preform was placed in an oven and then dried, and then hot-pressed and cured in a vulcanizer to obtain a Cu-TCPP modified carbon cloth reinforced resin-based friction material. The hot-pressing curing conditions were: temperature 190°C, pressure 6MPa, and curing time 8min. The friction coefficient of the Cu-TCPP modified carbon cloth reinforced resin-based friction material was 0.098; the wear rate was 5.43×10 -12 m 3 / (N·m).

[0049] Comparative Example 1 A method for preparing an unmodified carbon cloth reinforced resin-based friction material comprises the following steps: Step 1: Soak 4.5g of carbon fiber cloth in acetone at room temperature for 48 hours to remove surface sizing and impurities, wash it repeatedly with deionized water three to four times, and then dry it for use; Step 2: The carbon fiber cloth obtained in step 1 is subjected to oxidation treatment in a nitric acid solution with a volume fraction of 68%, and the reaction conditions are 90° C. and 3 h to enhance the active sites on the surface of the carbon fiber cloth, and then the carbon fiber cloth is repeatedly washed with deionized water and dried for later use; Step 3: Vacuum impregnate the carbon fiber cloth obtained in step 2 into a phenolic resin ethanol solution with a mass fraction of 24%, and the impregnation conditions are: the pressure is 0.09 MPa at room temperature and the impregnation time is 12 hours; Step 4: The impregnated preform is placed in an oven and then dried. It is then hot-pressed and cured in a vulcanizer to obtain an unmodified carbon cloth reinforced resin-based friction material. The hot-pressing curing conditions are: temperature 170°C, pressure 5MPa, and curing time 10min. The friction coefficient of the unmodified carbon cloth reinforced resin-based friction material is 0.091; the wear rate is 6.9×10 -12 m 3 / (N·m).

[0050] See also Figure 1 The SEM photos of the Cu-TCPP modified carbon cloth prepared in Example 1 of the present invention are shown, wherein (a) is the original carbon fiber cloth, and (b) is the Cu-TCPP modified carbon cloth prepared in Example 1. It can be seen from the figure that the surface of the original carbon fiber cloth is smooth, and there are narrow and shallow grooves after acetone treatment, and the surface of the Cu-TCPP modified carbon cloth after modification is covered with lamellar Cu-TCPP.

[0051] Figure 2 FTIR analysis of Cu-TCPP modified carbon cloth prepared in Example 1 of the present invention, wherein CF is the original carbon fiber cloth; CF / Cu-TCPP is the Cu-TCPP modified carbon cloth prepared in Example 1; Figure 2 It can be seen that after Cu-TCPP grafting, in addition to the characteristic peak of carbon fiber, the surface of the carbon fiber cloth -1 and 1402 cm -1 Two new peaks appeared nearby, which represent the OC-O-Cu bonds, indicating that Cu 2+ A coordination bond was formed between Cu-TCPP and the carboxyl group, indicating that Cu-TCPP was successfully grafted onto the carbon fiber.

[0052] Figure 3It is a continuous friction coefficient comparison diagram of the Cu-TCPP modified carbon cloth reinforced resin-based friction material prepared in Example 1 of the present invention and the unmodified carbon cloth reinforced resin-based friction material prepared in Comparative Example 1, wherein C1 is the unmodified carbon cloth reinforced resin-based friction material prepared in Comparative Example 1, and C2 is the Cu-TCPP modified carbon cloth reinforced resin-based friction material prepared in Example 1; it can be seen from the figure that after modification, the friction coefficient of the Cu-TCPP modified carbon cloth reinforced resin-based friction material is increased from 0.091 to 0.104, and the friction coefficient is increased by 14.3%.

[0053] Figure 4 The figure is a comparison of the wear rates of the Cu-TCPP modified carbon cloth reinforced resin-based friction material prepared in Example 1 of the present invention and the unmodified carbon cloth reinforced resin-based friction material prepared in Comparative Example 1, wherein C1 is the unmodified carbon cloth reinforced resin-based friction material prepared in Comparative Example 1, and C2 is the Cu-TCPP modified carbon cloth reinforced resin-based friction material prepared in Example 1; it can be seen from the figure that after modification, the wear rate of the Cu-TCPP modified carbon cloth reinforced resin-based friction material increases from 6.9×10 -12 m 3 / (N·m) decreased to 4.38×10 -12 m 3 / (N·m), the wear rate of the friction material decreased by 36.5% after grafting Cu-TCPP.

[0054] In summary, the present invention provides a method for preparing a Cu-TCPP modified carbon cloth reinforced resin-based friction material. The lamellar Cu-TCPP nanosheets are grown in situ on the surface of the carbon fiber cloth by solvent thermal reaction, which not only increases the roughness of the fiber surface and provides more mechanical meshing points for the carbon fiber and the resin matrix, but also the Cu-TCPP nanosheets themselves and the active functional groups (such as hydroxyl groups) introduced during the growth process can react chemically with the resin molecules to form stable chemical bonds, thereby greatly enhancing the interfacial bonding force between the carbon fiber and the resin. Due to the significant improvement in the interfacial bonding force between the carbon fiber and the resin matrix, the modified carbon cloth reinforced resin-based friction material can more effectively transfer stress when subjected to friction and wear, reduce crack propagation and peeling at the interface, thereby significantly improving the wear resistance and service life of the friction material. The introduction of Cu-TCPP nanosheets may also have a positive effect on the thermal stability and mechanical properties of the friction material. The presence of the nanosheets can hinder the rapid conduction of heat and improve the thermal resistance of the material. At the same time, its reinforcing effect also helps to improve the overall mechanical strength of the material. The process of the present invention is highly controllable. By adjusting the concentration of reactants, the conditions of the solvent thermal reaction and the subsequent processing steps, the growth morphology and distribution of the Cu-TCPP nanosheets can be accurately controlled, thereby meeting the specific requirements of the friction material performance in different applications. The solvents and cleaning agents (such as N, N-dimethylformamide and anhydrous ethanol) used are easy to recycle and treat, and the entire process does not involve the emission of toxic and harmful substances, which meets the requirements of environmental protection and sustainable development.

[0055] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A method for preparing a Cu-TCPP modified carbon cloth reinforced resin-based friction material, characterized in that: The following steps are involved: 1) Dissolve copper nitrate trihydrate and polyvinyl pyrrolidone in N,N-dimethylformamide to obtain a mixed solution A; dissolve meso-tetrakis(4-carboxyphenyl)porphine in anhydrous ethanol to obtain a mixed solution B; mix the mixed solution A and the mixed solution B, stir and react, and obtain a mixed solution C; 2) The pretreated carbon fiber cloth is sewn into a column and placed in the mixed solution C for solvothermal reaction. After the reaction is completed, it is washed alternately with anhydrous ethanol and N, N-dimethylformamide, and freeze-dried to obtain Cu-TCPP modified carbon cloth; 3) The Cu-TCPP modified carbon cloth is impregnated in a phenolic resin ethanol solution, dried, and then hot-pressed to obtain a Cu-TCPP modified carbon cloth reinforced resin-based friction material.

2. The method for preparing the Cu-TCPP modified carbon cloth reinforced resin-based friction material according to claim 1, characterized in that: In step 1), the usage ratio of copper nitrate trihydrate, polyvinyl pyrrolidone, N,N-dimethylformamide, meso-tetrakis(4-carboxyphenyl)porphine and anhydrous ethanol is (0.072-0.1152) g: (0.2-0.32) g: 45 ml: (0.08-0.128) g: 15 ml.

3. The method for preparing the Cu-TCPP modified carbon cloth reinforced resin-based friction material according to claim 1, characterized in that: In step 1), the rotation speed of the stirring reaction is 800-1000 r / min.

4. The method for preparing the Cu-TCPP modified carbon cloth reinforced resin-based friction material according to claim 1, characterized in that: In step 2), the pretreatment of the carbon fiber cloth includes: firstly soaking the carbon fiber cloth in acetone, washing it once with deionized water, drying it once, then oxidizing it in a nitric acid solution, washing it twice with deionized water, and drying it twice.

5. The method for preparing the Cu-TCPP modified carbon cloth reinforced resin-based friction material according to claim 4, characterized in that: In step 2), the soaking time is 48-76 hours; the mass fraction of the nitric acid solution is 68%; the temperature of the oxidation treatment is 75-95° C.; and the time is 3-5 hours.

6. The method for preparing the Cu-TCPP modified carbon cloth reinforced resin-based friction material according to claim 1, characterized in that: In step 2), the temperature of the solvent thermal reaction is 70-90° C. and the time is 12-24 hours.

7. The method for preparing the Cu-TCPP modified carbon cloth reinforced resin-based friction material according to claim 1, characterized in that: In step 3), the immersion pressure is 0.08-0.1 MPa, and the immersion time is 10-24 h.

8. The method for preparing the Cu-TCPP modified carbon cloth reinforced resin-based friction material according to claim 1, characterized in that: In step 3), the temperature of the hot pressing curing is 170-190° C., the pressure is 4-6 MPa, and the curing time is 8-10 min.

9. A Cu-TCPP modified carbon cloth reinforced resin-based friction material, characterized in that: The Cu-TCPP modified carbon cloth reinforced resin-based friction material is prepared by the preparation method of any one of claims 1 to 8, wherein the mass fraction of the resin in the Cu-TCPP modified carbon cloth reinforced resin-based friction material is 24%-26%.

10. Application of the Cu-TCPP modified carbon cloth reinforced resin-based friction material obtained by the preparation method of the Cu-TCPP modified carbon cloth reinforced resin-based friction material according to any one of claims 1 to 8 in vehicle braking.

Citation Information

Patent Citations

  • Method for preparing carbon fibers with surfaces grafted with hyperbranched polymer

    CN107266712A

  • Sizing agent for carbon fiber modification as well as preparation method and use method of sizing agent

    CN118186781A